ON THE PHASES OF CLINICAL COURSE AND TREATMENT OF SPINAL CORD AND SPINE INJURIES (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The study of the clinical course and treatment of spinal injuries is essential due to the high incidence and severity of these conditions, which require specialized management. This research categorizes spinal injuries into distinct clinical phases, including temporary clinical compensation, moderate and severe clinical decompensation, acquired clinical compensation, and clinical improvement. Each phase is marked by specific neurological, respiratory, and autonomic symptoms that guide treatment decisions. Early interventions, including surgical decompression, spinal stabilization, and ozone therapy for scar and adhesion prevention, have shown positive outcomes in patient recovery. This phased approach enables a tailored and effective treatment strategy, improving patient prognosis and enhancing quality of life.